Scedosporiosis in a Combined Kidney and Liver Transplant Recipient: A Case Report of Possible Transmission from a Near-Drowning Donor. (13th December 2016) - Leek, Rachael; Aldag, Erika; Nadeem, Iram; Gunabushanam, Vikraman; Sahajpal, Ajay; Kramer, David J.; Walsh, Thomas J.
Abstract : Scedosporium spp. are saprobic fungi that cause serious infections in immunocompromised hosts and in near-drowning victims. Solid organ transplant recipients are at increased risk of scedosporiosis as they require aggressive immunosuppression to prevent allograft rejection. We present a case of disseminated Scedosporium apiospermum infection occurring in the recipient of a combined kidney and liver transplantation whose organs were donated by a near-drowning victim and review the literature of scedosporiosis in solid organ transplantation.